THE EFFECT OF TRADITIONAL MUSIC THERAPY ON BLOOD PRESSURE AMONG ELDERLY WITH HYPERTENSION: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.103 - Ni Luh Putu Dian Yunita Sari; Etty Rekawati (International Journal of Nursing and Health Services (IJNHS), 2019)
Background: Elderly as one of vulnerable population has experienced several risk of cardiovascular system disturbance such as hypertension. Hypertension be non communicable disease most suffered elderly in some countries. Objective: This literature review aimed at describing the effect of traditional music therapy on blood pressure among elderly with hypertension. Method: This study carried out from databases such as EBSCOhost, Scopus, Pubmed, ProQuest, Science Direct and Sage with limited years of an article published in the last ten years (2008-2018). Result: Fifteen most relevant articles were extracted in this study and found that traditional music therapy provide a positive effect to decrease blood pressure’s elderly with hypertension and this finding explained clearly with Roy’s Adaptation Model. Conclusion: Traditional music therapy provides a positive effect in lowering blood pressure’s elderly with hypertension. This therapy can be given as single intervention or collaboration with other non pharmacological therapy such as calisthenics, breathing exercises, muscle relaxation, lifestyle modifications and walking-based exercise.